Isolated leptomeningeal carcinomatosis and possible fungal meningitis as late sequelae of oesophageal adenocarcinoma - Dumbill, Richard (BMJ Case Rep, 2019)
We describe a case of a 67-year-old man with known chronic obstructive pulmonary disease, type 2 diabetes mellitus, hypertension, osteoarthritis, previous history of excess alcohol intake, and oesophagectomy 3 years earlier for T3N0 adenocarcinoma, referred by his general practitioner with confusion, weight loss and several recent falls. CT of the chest, abdomen and pelvis revealed a right middle-lobe pulmonary embolism, while CT of the head revealed a communicating hydrocephalus. Lumbar puncture was performed, and empirical treatment for tuberculous and fungal meningitis was commenced. Unfortunately, he suffered a rapid neurological deterioration with markedly elevated cerebrospinal fluid (CSF) pressures, leading to an external ventricular drain. Cytological analysis of a CSF sample revealed a cellular infiltrate consistent with leptomeningeal carcinomatosis (adenocarcinoma), with the previous oesophageal malignancy the likely primary. He passed away 17 days after hospital admission. Prolonged culture of CSF later produced evidence of two distinct phaeomycotic moulds (Cladosporium sp and Exophiala sp), suggesting that fungal meningitis may also have contributed to the clinical picture.